2021
DOI: 10.3855/jidc.13419
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of COVID-19 Confirmed Cases in Indo-Pak Sub-Continent

Abstract: Introduction: The global COVID-19 pandemic originated from the Chinese city of Wuhan and gradually reached every end of the world. It has adversely affected economies of developed as well as underdeveloped countries, the subcontinent has been hit badly by the negative consequences of deadliest coronavirus. People are getting affected by the virus in large numbers and cases in growing on daily bases. Methodology: The present study employs Automatic ARIMA through R package “forecast”, to predict the growin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…However, in reality the figures were much higher. Similar studies have been performed by Tak et al (2021) and Maan et al (2022) on India, Yousaf et al (2020) for Pakistan and Aslam et al (2021) for a comparative study of India, Bangladesh and Pakistan. Ghosh et al (2020) take a unique approach to forecasting Covid Infections for India.…”
Section: Introductionsupporting
confidence: 58%
“…However, in reality the figures were much higher. Similar studies have been performed by Tak et al (2021) and Maan et al (2022) on India, Yousaf et al (2020) for Pakistan and Aslam et al (2021) for a comparative study of India, Bangladesh and Pakistan. Ghosh et al (2020) take a unique approach to forecasting Covid Infections for India.…”
Section: Introductionsupporting
confidence: 58%
“…Here we mention few but not limited to the readers, for instance, Aslam [12] used a kalman filter with autoregressive integrated moving average (ARIMA) model for forecasting the prevalence, recoveries, deaths and active cases related to COVID-19 in Pakistan. Aslam, Awan [13] also used ARIMA model and forecast the COVID-19 confirmed cases in Pakistan, India and Bangladesh. Chaudhry, Hanif [14] used SPSS series expert modeller and forecast the COVID-19 cases in Pakistan and concluded that rising trend is expected in COVID-19 cases.…”
Section: Trend Analysis Of Covid-19 Cases In Pakistanmentioning
confidence: 99%
“…In particular, in our works [6][7][8][9][10][11], it was noted that specialists in the field of physical and mathematical sciences make an important contribution to research on the spread of the new coronavirus COVID-19. Works on statistical analysis [2][3][4][5][12][13][14][15], forecasting [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32], forecasting systematization [33,34], spatial-temporary modeling of the spread of the new coronavirus [35][36][37][38] etc. was actively continuing in 2021.…”
Section: Introductionmentioning
confidence: 99%